An Appraisal System Analysis of Andrew Tate Interview on YouTube - Muhammad Yovan Yoxan; Ela Martisa (ELITE: Journal of English Language and Literature, 2024)
This study discusses the Appraisal system contained in Andrew Tate's interview with Laiyah Heilpern. This study aims to describe the use of appraisal attitude systems. The study used a descriptive qualitative method. Data collection techniques are done by downloading, reading, watching, identifying, and coding. The data derived from Andrew Tate's interview contained on YouTube, especially utterances that contain an appraisal system. The result shows that there are 26 data of appraisal systems used by Andrew Tate, which indicates that effect is often employed to convey affective responses. The judgment also used relevant appraisal criteria to evaluate the situation being evaluated. It also reveals that appreciation is used to highlight aspects that are considered valuable in the appraisal attitude system in Andrew Tate's interview.